Desenvolvimento reprodutivo de ratos machos expostos ao agente hipolipemiante rosuvastatina - Leite, Gabriel Adan Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Dyslipidemias are frequently found in children due to obesity, bad eating habits and the lack of physical exercises. Rosuvastatin acts as an HMG-CoA reductase inhibitor and has been indicated to prevent cardiovascular diseases and to treat dyslipidemias due to its higher efficiency to reduce serum cholesterol concentrations. This study aimed to investigate initial sexual development and the possible reproductive adverse effects on sexual maturity due to juvenile male rats exposure to rosuvastatin during prepuberty. Three groups were formed with newly weaned rats (n= 20/per group): control, whose rats received saline solution 0.9%, rosuvastatin at doses of 3 or 10 mg/Kg daily by gavage, since post-natal day (PND) 21 until puberty onset. Part of each group (n=10/per group) was euthanized on PND55 and the remaining rats (n=10/per group) were maintained until sexual maturity and were euthanized on PND110. On PND55, we analyzed the hormonal concentrations, testicular and epididymal histology and the expression of androgen receptors (AR) on testis and epididymis. During sexual maturity, the parameters evaluated were sexual behavior, hormonal concentrations, sperm production, morphology and motility, besides testicular and epididymal histology and immunohistochemistry for AR. In the rosuvastatin-treated groups, the results demonstrated a trend towards a decrease in testosterone concentration, but below the significance level, as well as delays in both the age of puberty onset and in epididymal development. There were also testicular alterations that might be related to delayed puberty and decrease of serum testosterone. In the adulthood, the rosuvastatin-treated groups showed diminution in follicle-stimulating hormone (FSH), luteinizing hormone (LH) and testosterone concentrations, delay in the latency to the first penis intromission, pathologic alterations on testis and epididymis and decreased sperm ...

As dislipidemias têm sido frequentemente encontradas nas crianças e adolescentes devido a obesidade, maus hábitos alimentares e a falta de exercícios físicos. A rosuvastatina atua como inibidor da enzima HMG-CoA redutase e pode ser indicada para a prevenção de doenças cardiovasculares e para o tratamento das dislipidemias, devido a sua grande eficiência na redução das concentrações plasmáticas do colesterol sérico. Este estudo pretendeu investigar o desenvolvimento sexual inicial e os possíveis efeitos reprodutivos adversos na maturidade sexual decorrentes da exposição de ratos juvenis à rosuvastatina na pré-puberdade. Foram formados três grupos aleatoriamente com ratos recém-desmamados (n= 20/por grupo): grupo controle, que recebeu solução salina 0.9%, e os grupos tratados com 3 ou 10 mg/Kg de rosuvastatina por dia via gavagem, desde o dia pós-natal (DPN) 21 até a instalação da puberdade. Parte dos animais de cada grupo (n=10/por grupo) foi eutanasiada no DPN55 e os animais remanescentes foram mantidos até a maturidade sexual e foram eutanasiados no DPN110. No DPN55 foram avaliados as concentrações hormonais, histologia testicular e epididimária e expressão de receptores de andrógenos (AR) no testículo e epidídimo. Na maturidade sexual foram avaliados o comportamento sexual, concentrações hormonais, produção, morfologia e motilidade dos espermatozóides, além da histologia do testículo e epidídimo e imunohistoquímica para AR no testículo. Nos grupos tratados com rosuvastatina, os resultados demonstraram uma tendência para a diminuição das concentrações de testosterona, mas abaixo do nível de significância, bem como houve atraso na idade da instalação da puberdade e no desenvolvimento epididimário. Houve ainda alterações testiculares que podem estar relacionadas com o atraso na puberdade e a diminuição da testosterona. Na maturidade sexual, os animais ...
Keywords: Hipolipemiantes; Reprodução; Toxicologia; Antilipemic agents